Chemical speciation of metal complexes from chemical shift calculations: The interaction of 2-amino-N-hydroxypropanamide with V(V) in aqueous solution - Duarte, Helio Anderson; Vankova, Nina; Ferreira, Isabella Pires; Paniago, Eucler B.; Heine, Thomas (Journal of Physical Chemistry B, 2013)
The chemical speciation of 2-amino-N-hydroxypropanamide (β-alaninohydroxamic acid, HL) and vanadium (V) in aqueous solution has been investigated through calculations of the thermodynamic properties and the 51V nuclear magnetic resonance (NMR) chemical shifts of the species formed at equilibrium. The results have been compared directly with the experimental 51V NMR data. The 51V NMR chemical shifts have been calculated by using a density functional theory (DFT) approach accounting for relativistic corrections and solvent effects. All tautomers of the 1:1 and 1:2 VO2+/β-ala complexes with different degrees of protonation have been calculated and thermodynamic and structural properties are presented for the most stable species. The system is better modeled as tautomeric equilibria, and species lying down in the range of 10 kcal·mol-1 cannot be neglected at the BP/TZ2P/COSMO approach. In fact, the metal complex speciation in aqueous solution should not be investigated based solely on the thermodynamic analysis, but together with spectroscopic calculations such as NMR. © 2013 American Chemical Society.
CRIS-Team Scopus Importer:2023-03-20